FRI0603 Synovial Fluid Analysis and Crystal Detection: Results from a Cohort of Possible Artropathic Consecutive Patients with Effusion. (9th June 2015) - Montagna, P.; Brizzolara, R.; Trombetta, A.C.; Soldano, S.; Ferrone, C.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Among rheumatic diseases, gout and pseudogout result from the presence of specific crystals in the synovial fluid (SF) of inflamed joints, monosodium urate (MSU) and calcium pyrophosphate dehydrate (CPPD) crystals, respectively. Crystal detection and identification by a compensated polarized microscope allows a quick and definitive diagnosis of both gout and CPPD arthritis, and it is the accepted gold standard (1, 2). SF examination allows to identify a variety of other crystals and particles that can induce arthropathy (3). Objectives: To study a cohort of patients with SF effusion, according to specific crystal types detected. Methods: Arthrocentesis was performed in 589 patients for cytological evaluation and crystal detection. For crystal detection, SF was examined by a compensated polarized microscope (400x), initially under ordinary light, subsequently under simple polarized light, finally adding a first-order red compensator to allow crystal identification by their birefrangence (2). SFs were divided into 5 groups, according to crystal type found: MSU, CPPD, apatite, aspecific crystals and without crystals. According to leukocyte count, SFs were divided into non-inflammatory (leukocytes <2000/μl), moderately inflammatory (between 2000/μl and 5000/μl), inflammatory (between 5000/μl and 50000/μl) and highly inflammatory or infectious (>50000/μl). Statistical analysis was performed by χ 2 and Mann-Whitney tests. Results: Of the 589 patients considered, 298 (50, 6%) were males and 291 (49, 4%) females, mean age was 69.18±17.3 yrs. Aspirated joints were: knee (487 patients), elbow (29 patients), shoulder (28 patients), 1 MTP joint (23 patients), ankle (4 patients), hand (9 patients) and wrist (9 patients). Of note, the subdivision in groups by leukocyte count showed a significant association between the presence of MSU crystals and 5000-50000/ml counts (p=0.03) (Table ). The increase in the number of leukocytes significantly correlates with the presence of CPPD crystals (p=0.01) (Figure ). A significant correlation was also observed between leukocyte count <2000/ml and the different groups (MSU, apatite, aspecific crystals and no crystals: p=0.02, p=0.006, p=0.02, p=0.02 respectively) (Table ). Conclusions: This study confirms that a high leukocyte count in SF suggests the presence of gout and pseudogout, according to literature data (4). Moreover, SF analysis was confirmed as important also in patients whit a mild joint inflammation. References: Reginato A et al. Clin Geriatr Med 1988;4:295. 2. Pascual E et al. Cur Opin Rheumatol 2011;23:161-69. 3. Pascual E et al. Ann Rheum Dis 2007;66:1056-58. 4. Dougados M. Bailliere's Clin Rheumatol 1996;10:519-34. Disclosure of Interest: None declared